Can We Optimize Antibiotic Use in Norwegian Neonates? A Prospective Comparison Between a University Hospital and a District Hospital - Thaulow, Christian Magnus; Berild, Dag; Blix, Hege Salvesen; Brigtsen, Anne Karin; Myklebust, Tor Åge; Eriksen, Beate Horsberg (Frontiers in Pediatrics, 2019)
Background: Worldwide, a large proportion of neonates are prescribed antibiotics without having infections leading to increased antimicrobial resistance, disturbance of the evolving microbiota and increasing the risk of various chronical diseases. Comparing practice between different hospitals/settings is important in order to optimize antibiotic stewardship. Aim: To investigate and compare the potential for improved antibiotic stewardship in neonates in two Norwegian hospitals with different academic culture, with emphasis on antibiotic exposure in unconfirmed infections, treatment length/doses, CRP values and the use of broad-spectrum antibiotics (BSA). All types of infections were investigated, but the main focus was on early-onset sepsis (EOS). Methods: We conducted a prospective observational cohort study of antibiotic use in a Norwegian university hospital (UH) and a district hospital (DH), 2017. Unconfirmed infections were defined as culture negative infections that neither fulfilled the criteria for clinical infection (clinical symptoms, maximum CRP >30 mg/L, and treatment for at least five days). Results: Ninety-five neonates at the DH and 89 neonates at the UH treated with systemic antibiotics were included in the study. In total, 685 prescriptions (daily doses) of antibiotics were given at the DH and 903 at the UH. Among term and premature infants (≥ 28 weeks), 82% (75% at the UH and 86% at the DH, p= 0.172) of the treatments for suspected EOS were for unconfirmed infections, and average treatment length in unconfirmed infections was 3.1 days (both hospitals). Median dose for aminoglycoside was higher for term infants at the UH (5.96, 95% CI 5.02-6.89) compared to the DH (4.98, 95% CI 4.82-5.14) (p<0.001). At the UH, all prescriptions with aminoglycosides were gentamicin, while tobramycin accounted for 93% of all prescriptions with aminoglycosides at the DH. Conclusion: There is a potential for reduction in both antibiotic exposure and treatment length in these two neonatal units, and a systematic risk/observational algorithm of sepsis should be considered in both hospitals. We revealed no major differences between the UH and DH, but doses and choice of aminoglycosides varied significantly.